Psychic distance and FDI in Turkey: the role of industrial development and religion. (27th June 2020) - Jimenez, Alfredo; Eren, Mesut; Bayraktar, Secil
Our paper analyses the critical role of psychic distance on Foreign Direct Investments (FDI) in an emerging economy, Turkey. Our results demonstrate that two psychic distance dimensions are significant when analysing FDI flows from OECD countries. First, psychic distance in industrial development has a positive effect, namely, greater industrial development distance between the investor country and Turkey increases FDI flows. Second, psychic distance in religion plays a negative role whereby greater distance between the investor country and Turkey reduces FDI flows. In addition, home country Gross Domestic Product (GDP) and European Union (EU) membership positively affect foreign investments in Turkey. By contrast, and as expected, geographic distance has a negative effect.